2019
DOI: 10.1021/acs.jafc.9b00058
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Induces Disease Resistance to Botrytis cinerea in Tomato Fruit by Activating Jasmonic Acid Signaling Pathway

Abstract: Melatonin acts as a crucial signaling molecule with multiple physiological functions in plant response to abiotic and biotic stresses. However, the impact and regulatory mechanism of melatonin on attenuating tomato fruit fungal decay are unclear. In this study, we investigated the potential roles of melatonin in modulating fruit resistance to Botrytis cinerea and explored related physiological and molecular mechanisms. The results revealed that disease resistance was strongly enhanced by melatonin treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(100 citation statements)
references
References 57 publications
4
96
0
Order By: Relevance
“…Furthermore, results from some investigations support the hypothesis that melatonin increases phagocytic activity and decreases oxidative stress during candidiasis [60][61][62]. In a plant-fungi interaction model, melatonin played a promotional role in the resistance of tomato fruit to Botrytis cinerea via the regulation of H 2 O 2 generation and the jasmonic acid signaling mechanism [63]. Melatonin can increase fungicide susceptibility, enhance vulnerability of Phytophthora infestans to different environmental stress, decrease the dosage level, and promote the efficiency of fungicide treatment against potato late blight [64].…”
Section: Antifungal Effect Of Melatoninmentioning
confidence: 67%
“…Furthermore, results from some investigations support the hypothesis that melatonin increases phagocytic activity and decreases oxidative stress during candidiasis [60][61][62]. In a plant-fungi interaction model, melatonin played a promotional role in the resistance of tomato fruit to Botrytis cinerea via the regulation of H 2 O 2 generation and the jasmonic acid signaling mechanism [63]. Melatonin can increase fungicide susceptibility, enhance vulnerability of Phytophthora infestans to different environmental stress, decrease the dosage level, and promote the efficiency of fungicide treatment against potato late blight [64].…”
Section: Antifungal Effect Of Melatoninmentioning
confidence: 67%
“…A large number of genes, involved in MAPK signaling, nucleotide metabolism, and ethylene biosynthesis, are transcriptionally reprogrammed by melatonin treatment, suggesting the possible role of melatonin as a signal molecule (Xu et al, 2017). Furthermore, exogenous melatonin treatment could promote methyl jasmonate (MeJA) accumulation and enhance the expression of proteinase inhibitor II in tomato fruits, which results in the up-regulation of JA defense signaling that is a crucial pathway in pathogen resistance (Liu et al, 2019). Other studies showed that melatonin is involved in abscisic acid and cytokinin metabolic signaling pathways regulating heat stress response in perennial ryegrass (Zhang et al, 2017a), and participates in adventitious root development by regulating auxin and nitric oxide signaling in tomato plants (Wen et al, 2016).…”
Section: Mechanisms Of Exogenous Melatonin Functions In Post-harvest mentioning
confidence: 99%
“…As the most commonly known members of phytohormones, Jasmonic acid (JA) signaling pathways were reported to have an active effect on inhibiting gray mold ( Liu et al., 2019 ). It was generally believed that activating of JA signaling pathway can induce resistance against necrotrophs ( Liu et al., 2019 ) and endogenous contents of JAs was rapidly up-regulated and then triggered the formation of COI1-JA-JAZ ternary complex to induce degradation of the Jasmonate-ZIM domain (JAZ) proteins ( Zhang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the most commonly known members of phytohormones, Jasmonic acid (JA) signaling pathways were reported to have an active effect on inhibiting gray mold ( Liu et al., 2019 ). It was generally believed that activating of JA signaling pathway can induce resistance against necrotrophs ( Liu et al., 2019 ) and endogenous contents of JAs was rapidly up-regulated and then triggered the formation of COI1-JA-JAZ ternary complex to induce degradation of the Jasmonate-ZIM domain (JAZ) proteins ( Zhang et al., 2019 ). The basic helix-loop-helix (bHLH) transcription factor MYC2 acted as a key regulator in the JA signaling pathway ( Boter et al., 2004 ; Lorenzo et al., 2004 ; Dombrecht et al., 2007 ) and transcriptional activity of MYC2 was repressed by JAZ ( Chini et al., 2007 ; Thines et al., 2007 ; Pauwels et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%